CD215+ Myeloid Cells Respond to Interleukin 15 Stimulation and Promote Tumor Progression - Lin, Shouheng; Huang, Guohua; Xiao, Yiren; Sun, Wei; Jiang, Yuchuan; Deng, Qiuhua; Peng, Muyun; Wei, Xinru; Ye, Wei; Li, Baiheng; Lin, Simiao; Wang, Suna; et al. (Frontiers in Immunology, 2017)
Interleukin 15 (IL-15) regulates the development, survival, and functions of multiple innate and adaptive immune cells and plays a dual role in promoting both tumor cell growth and antitumor immunity. Here, we demonstrated that the in vivo injection of recombinant human IL-15 (200 µg/kg) or murine IL-15 (3 µg/kg) to tumor-bearing NOD-SCID-IL2Rg−/− (NSI) mice resulted in increased tumor progression and CD45+ CD11b+ Gr-1+ CD215+ cell expansion in the tumors and spleen. In B16F10-bearing C57BL/6 mice model, we found that murine IL-15 has antitumoral effect since the activation and expansion of CD8+ T cells with murine IL-15 treatment. But no enhanced or reduced tumor growth was observed in mice when human IL-15 was used. However, both murine and human IL-15 promote CD45+ CD11b+ Gr-1+ CD215+ cells expansion. In xenograft tumor models, CD215+ myeloid cells, but not CD215− cells, responded to human IL-15 stimulation and promoted tumor growth. Furthermore, we found that human IL-15 mediated insulin-like growth factor-1 production in CD215+ myeloid cells and blocking IGF-1 reduced the tumor-promoting effect of IL-15. Finally, we observed that higher IGF-1 expression is an indicator of poor prognosis among lung adenocarcinoma patients. These findings provide evidence that IL-15 may promote tumor cell progression via CD215+ myeloid cells, and IGF-1 may be an important candidate that IL-15 facilitates tumor growth.